Interdependencies of demand for international air transportation and international tourism. (December 2016) - Divisekera, Sarath
This article analyses the interdependency of demand for two of the leading traded services globally: international travel (transportation) and international tourism. Based on the Almost Ideal Demand System, the study models transport and tourism demand simultaneously for a range of countries: Australia, New Zealand, the United States and the United Kingdom. Overall, tourism demand is found to be more expenditure and price-elastic than is the demand for transport services to the same destination. The cross-price elasticities indicate significant interdependencies of demand between transport and tourism, and between destinations. Overall, the cross-price elasticities confirm the complementarity between transport demand and tourism demand. However, in the cases of the UK demand for the United States and the US demand for the United Kingdom, substitutability between the two demand types is found.